Effect of process variables on structure and properties of aluminium–silicon piston alloy - Haque, Mohafizul Md; Maleque, Md. Abdul (Elsevier BV, 1998)
The majority of automotive pistons are cast in one of the groups of low expansion Al–Si eutectic alloys. The structure and mechanical properties of these alloys are highly ependent upon cooling rate, composition, modification and the heat-treatment operations. The effect of these variables were investigated in this study, using locally available automotive ‘scrap pistons’ as basic raw materials. Strontium master alloy was used as the source of the modifier and a natural-gas-fired crucible furnace was used for melting purposes. The microstructures of the alloy, both in the modified and unmodified conditions, were studied in this investigation. Properties such as the ultimate tensile strength (UTS), percentage elongation, hardness and percentage porosity for both rates of cooling have been determined, both with and without the addition of strontium. Significant changes in structures were observed to occur, especially in the primary and eutectic silicon phases. Full heat treatment has also shown a great influence on the structure and properties of the aluminium–silicon piston alloy. The residual stress in the modified alloy is fully relieved due to thermal treatment. Finally, attempts were made to correlate the observed structures and properties obtained during the experiment.